Employability Pathways in Tertiary Education: Insights from Cambodian Undergraduates - Long Bunteng (jfpublisher, 2026)
This study investigates the institutional factors that influence students' perceptions of their employability in higher education institutions in Cambodia. A structured questionnaire disseminated over social media sites like Telegram and Messenger was used to gather data for a quantitative study design. A non-probability sampling strategy that included quota, convenience, and purposive sampling was used to guarantee representation among student cohorts and academic disciplines. Using a five-point Likert scale ranging from